PENGARUH LINGKUNGAN KERJA FISIK DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS TENAGA KERJA KOTA TANGERANG SELATAN - Zaffira; Yunanti, Siska (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the physical work environment, physical work environment, and organizational culture on performance at the South Tangerang City Manpower Office. Method method used Quantitative. Sampling technique used is a saturated sample which amounted to 77 respondents. Tests used validity test, reliability test reliability, classical assumption test, linear regression test, correlation coefficient test, test the coefficient of determination, hypothesis test (t test and f test). The results of the research environment, physical work environment and organizational culture have a positive and significant effect on employee performance with a regression equation Y = 4.5.employee performance with the regression equation Y = 4.379 +0.178 X1 + 0.705X2. The simultaneous correlation coefficient is 0, 893 or 89.3%.meaning that the two variables have a strong level of relationship. Determination value or contribution of 79.8% the rest by 20.2% Hypothesis testing obtained Fcount value 46.374> F table 3.120 with a significant level of 0.000 <0.05.